2015
DOI: 10.1371/journal.pone.0134895
|View full text |Cite
|
Sign up to set email alerts
|

Inaccessible Biodiversity on Limestone Cliffs: Aster tianmenshanensis (Asteraceae), a New Critically Endangered Species from China

Abstract: Aster tianmenshanensis G. J. Zhang & T. G. Gao, a new species of Asteraceae from southern China is described and illustrated based on evidence from morphology, micromorphology and molecular phylogeny. The new species is superficially similar to Aster salwinensis Onno in having rosettes of spatulate leaves and a solitary, terminal capitulum, but it differs by its glabrous leaf margins, unequal disc floret lobes and 1-seriate pappus. The molecular phylogenetic analysis, based on nuclear sequences ITS, ETS and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 19 publications
4
29
0
1
Order By: Relevance
“…nrDNA ITS, ETS and cpDNA trnL-F have become the most frequently used molecular markers for phylogenetic studies of the tribe Astereae (Markos and Baldwin 2001, Fiz et al 2002, Li et al 2012, Jafari et al 2015, Zhang et al 2015, Xiao et al 2019. Our phylogenetic results showed that two samples of the new taxon formed a monophyletic group (ML = 100, PP = 1.00 in Fig.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…nrDNA ITS, ETS and cpDNA trnL-F have become the most frequently used molecular markers for phylogenetic studies of the tribe Astereae (Markos and Baldwin 2001, Fiz et al 2002, Li et al 2012, Jafari et al 2015, Zhang et al 2015, Xiao et al 2019. Our phylogenetic results showed that two samples of the new taxon formed a monophyletic group (ML = 100, PP = 1.00 in Fig.…”
Section: Discussionmentioning
confidence: 61%
“…The sequences of the nrDNA ITS, ETS and plastid DNA trnL-F were used in phylogenetic analyses and their boundaries were determined according to Li et al (2012). Our combined data set contained a total 183 DNA sequences; most of these were downloaded from GenBank (Li et al 2012, 2017, Zhang et al 2015, Xiao et al 2019), but 13 accessions were newly sequenced for this study. The sequences were initially aligned using Clustal X ver.…”
Section: Molecular Systematicsmentioning
confidence: 99%
“…The ITS, ETS and trnL-F sequences were selected as molecular markers to generate the datasets. According to previous studies (Li et al, 2012;Zhang et al, 2015), the systematic position of shrub and alpine Aster groups are distinct from the core Aster (sensu Zhang et al, 2015; including the type of genus, Aster amellus) and may represent separate genera.…”
Section: Taxon Samplingmentioning
confidence: 90%
“…Five samples of the potential new taxon and six of the superficially similar Aster dolichophyllus were added in this study. The taxonomic treatment in the Flora of China and the definitions of Aster and "core Aster" in our previous study (Zhang et al, 2015) were followed. In the phylogenetic analysis, PeerJ reviewing PDF | (2018:08:30777:1:1:NEW 6 Dec 2018)…”
Section: Taxon Samplingmentioning
confidence: 99%
See 1 more Smart Citation